Fracture toughness and crack-resistance curve behavior in metallic glass-matrix composites - Launey, M. E.; Hofmann, D. C.; Suh, J. -Y.; Kozachkov, H.; Johnson, W. L.; Ritchie, R. O. (AMER INST PHYSICS, 2009)
Nonlinear-elastic fracture mechanics methods are used to assess the fracture toughness of bulk metallic glass (BMG) composites; results are compared with similar measurements for other monolithic and composite BMG alloys. Mechanistically, plastic shielding gives rise to characteristic resistance-curve behavior where the fracture resistance increases with crack extension. Specifically, confinement of damage by second-phase dendrites is shown to result in enhancement of the toughness by nearly an order of magnitude relative to unreinforced glass.
Keywords: BULK AMORPHOUS-ALLOYS; TENSILE DUCTILITY; FLOW; PLASTICITY